Social Network Analysis in #PialaKemenpora: A Dinamics of Social System - Harjo, Indhar Wahyu Wira; Mahendra , Rizky Adha (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
The suspension of sports competitions due to the Covid-19 pandemic has elicited mixed reactions from the public. On one hand, some individuals have expressed their support for the decision, while others have expressed theiropposition. This study aimed to examine the impact of the suspension on social networks, specifically the changes that occurred within themThe suspension of sports competitions due to Covid-19 has elicited mixed reactions from the public. This study aimed to examine the impact of the suspension on social networks, focusing on the changes that occurred within them. Specifically, the research analyzed the adjustments within the social network system that arose from the Piala Kemenpora (Menpora Cup) hashtag on Twitter (X). Academic research must explore changes in the social system, particularly the standing of key players and the nature of conversations in constantly evolving social networks. Using a qualitative research method and network analysis approach, data were collected during the Piala Kemenpora football competitions. The findings revealed a shift in the dominant actor throughout the competition, emphasizing the dynamic nature of competition and the importance of adapting to changing circumstances. Various actors, including mass media, competition organizers, football players, and politicians, took turns as the dominant actors, conveying distinct messages based on their respective interests, both supporting and criticizing the first football competition held in Indonesia during the Covid-19 pandemic. The diverse range of dominant actors in the first football competition held in Indonesia during the pandemic underscores the importance of adaptability and resilience in responding to changing circumstances in any competitive environment. The dominant actors' messages and the prevalent content of the social networks demonstrated the dynamics of the social systems based on the communication process of the connected actors.